Evaluating Enterprise Architecture Frameworks for Digital Transformation in Agriculture - Anbananthen K.S.M.; Muthaiyah S.; Thiyagarajan S.; Balasubramaniam B.; Yousif Y.B.; Mohammad S.; Kalid K.S. (Ital Publication, 2025)
This study aims to identify the most suitable Enterprise Architecture (EA) framework for driving digital transformation within Malaysia's agricultural sector. The objective is to evaluate and compare four leading EA frameworks?the Zachman Framework (ZFEA), the Department of Defense Architecture Framework (DoDAF), the Federal Enterprise Architecture Framework (FEAF), and The Open Group Architecture Framework (TOGAF)?using eight key criteria: adaptability, scalability, ease of implementation, support for modern technologies, cost-effectiveness, compliance, traceability, and risk management. A systematic comparative analysis assessed these frameworks' effectiveness in addressing the agricultural sector's specific needs. The findings indicate that TOGAF is the most appropriate framework due to its high adaptability, scalability, and robust support for modern technologies, making it ideal for the sector's requirements. In contrast, ZFEA, though versatile, faces significant challenges in practical implementation and scalability. DoDAF?s defense-centric focus limits its applicability in agriculture, and while FEAF is adaptable, it lacks strong support for modern technological integration. This study provides novel insights and practical recommendations for policymakers and practitioners to select the most effective EA framework, thereby supporting Malaysia's agricultural sector's digital transformation and modernization. ? Authors retain all copyrights.